2015
DOI: 10.1016/j.kijoms.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Studies on interaction of ribonucleotides with zinc ferrite nanoparticles using spectroscopic and microscopic techniques

Abstract: Interaction of ribonucleotides with zinc ferrite nanoparticles (~15 nm) prepared by the solegel method was studied at physiological pH (~7.0). Ultra-violet (UVeVis), Fourier transform infrared (FT-IR), Raman spectroscopy and field emission scanning electron microscopy (FE-SEM) and atomic force microscopy (AFM) were employed to investigate the interaction of ribonucleotides with zinc ferrite surface. Langmuir and Freundlich adsorption models were used to describe the equilibrium isotherms in the concentration r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…Although several metal oxides have been used in previous oligomerization studies, to the best of our knowledge this important group of binary oxide minerals has not yet been tested. The experimental findings reported here, in relation to the latest use of spinel ferrite for the entrapment of ribonucleotides on its surface [ 46 , 47 ], further sheds light on the role of spinel ferrites during the prebiotic chemistry epoch.…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although several metal oxides have been used in previous oligomerization studies, to the best of our knowledge this important group of binary oxide minerals has not yet been tested. The experimental findings reported here, in relation to the latest use of spinel ferrite for the entrapment of ribonucleotides on its surface [ 46 , 47 ], further sheds light on the role of spinel ferrites during the prebiotic chemistry epoch.…”
Section: Introductionmentioning
confidence: 63%
“…Some selected techniques of the material’s characterization have been described briefly in this article. Details of the material’s characterization have been reported in our previous work [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…The FTIR spectra were interpreted based on band assignments for nucleobase, nucleoside, and nucleotides in solution as reported previously in the literature. , The bands between ∼1000 and 1180 cm –1 correspond to PO 4 bands of the mononucleotide (Figure ). These bands overlap to some extent with the ribose bands between 960 and 1100 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…From the structure of inosine and cytidine, it is observed that inosine is a purine, while cytidine is a pyrimidine. There have been many previous reports showing that purine nucleotides had a greater binding affinity to zinc containing nanoparticles than pyrimidines probably due to the large number of electrons in the purine double-rings as compared to single-rings of pyrimidines. Thus, for torula yeast RNA, we speculate that the lack of inosine group could be the reason for its low binding ability with ZnO.…”
Section: Discussionmentioning
confidence: 99%